2011
DOI: 10.1016/j.jcmg.2010.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Iodine-123 mIBG Imaging for Predicting the Development of Atrial Fibrillation

Abstract: cardiac SNS abnormality was associated with the occurrence of both HF and permanent AF in paroxysmal AF patients, and (123)I-mIBG imaging may be a useful modality for predicting the development of AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 29 publications
1
25
0
3
Order By: Relevance
“…We recently reported on the risk factors which perpetuated AF in patients with paroxysmal AF, 14 but the risk factors for the transition from paroxysmal to permanent forms of AF are not the same as those for the late AF recurrence after intervention therapy. A recent report from a National Heart, Lung, and Blood Institute workshop has recommended research on the factors that influence secondary prevention delaying AF recurrence.…”
Section: Clinical Perspective On P 531mentioning
confidence: 99%
“…We recently reported on the risk factors which perpetuated AF in patients with paroxysmal AF, 14 but the risk factors for the transition from paroxysmal to permanent forms of AF are not the same as those for the late AF recurrence after intervention therapy. A recent report from a National Heart, Lung, and Blood Institute workshop has recommended research on the factors that influence secondary prevention delaying AF recurrence.…”
Section: Clinical Perspective On P 531mentioning
confidence: 99%
“…The main findings were as follows: [1] patients with heart failure tended to have decreased sympathetic nervous distribution (lower H/M 15 min ) and enhanced sympathetic tone (higher WR) at baseline; [2] neither sympathetic nervous distribution nor its tone changed post-ablation in the majority of patients; [3] among those with heart failure, an attenuation of excessive sympathetic nervous tone was observed (decrease in WR) post-ablation; [4] among those without heart failure, the sympathetic nervous tone became slightly enhanced (increase in the WR and decrease in the H/M 240 min ) postablation; and [5] a residual high sympathetic tone post-ablation independently predicted AF recurrence.…”
Section: Discussionmentioning
confidence: 97%
“…Scintigraphy with cardiac iodine-123-metaiodobenzylguanidine ( 123 I-mIBG) enables the reliable visualization of abnormal behavior of norepinephrine at sympathetic nerve endings and has been used in several studies to assess sympathetic nervous dysfunction such as AF and heart failure [1][2][3]. Here, we investigated the impact of AF ablation on the cardiac sympathetic nervous system using 123 I-mIBG scintigraphy in AF patients with and without heart failure.…”
Section: Background/objectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Akutsu et al 155 found that in HF patients with paroxysmal atrial fibrillation (AF), a decreased H/M was independently predictive of transition to permanent AF.…”
Section: Autonomic Imaging In Other Conditionsmentioning
confidence: 99%